Islam Dan Terorisme : Menelusuri Jejak Gerakan Jamaah Islamiyah (JI) Di Indonesia Tahun 1993 – 2024 - ilham maulana (Tamadduna: Jurnal Peradaban, 2025)
This article discusses the relationship between Islam and terrorism with a focus on the Jemaah Islamiyah (JI) movement in Indonesia in the period 1993 – 2024. This research aims to trace the history, development and socio-political impacts caused by JI's activities in Indonesia. This research method is library research, through research steps carried out, namely primary and secondary data collection, data management and writing. JI's existence cannot be separated from its connection to a pre-existing group, namely the Indonesian Islamic State. The JI movement is quiet and non-frontal through conditioning on collecting funds from members and trying to recruit new members. The results of this research show that the Jemaah Islamiyah organization was founded in 1993 and stated that it would disband in 2024. The movement carried out by JI was motivated by an attitude that declared war on all forms of discrimination against Islam as well as opposing all policies issued by the government. Indonesia and its peak was carrying out actions which they thought were jihad against disbelief but were declared by the state as a terrorist organization. This research is important to be used as a basic reference for the development of historical science, especially in exploring knowledge about the existence of organizations and their movements, especially in terms of threatening the integrity of the unitary state of the Republic of Indonesia.